Newcomers Navigating the Welfare State Experiences of Immigrants and Street-Level Bureaucrats with Belgium's Social Assistance System - Vandermeerschen, Hanne; Mescoli, Elsa; Lafleur, Jean-Michel; De Cuyper, Peter (Leuven University Press, 2023)
The needs of newcomers and the provided social assistance. The topic of social assistance for migrant newcomers often sparks heated public debate and remains a prominent concern on the policy agenda. Society has experienced a growing level of diversity. This reality gives rise to new demands and changing profiles of individuals who benefit from welfare services. Welfare institutions, which are responsible for providing social assistance, play a crucial role in granting access to social benefits for newcomers. Moreover, the provision of social assistance can significantly influence the settlement and integration processes of migrants. This book provides empirical insights into the alignment between the needs of newcomers and the service provided to them. It examines the accessibility of social assistance for newcomers from a comprehensive perspective, encompassing aspects such as gaining access (including equal access for all) and service availability. By focusing on the Belgian Public Centres for Social Welfare as a case study, the authors explore the policies and practices related to social assistance and labour market activation for newcomers and the factors that influence individuals' access to their rights. By incorporating the perspectives of all the relevant stakeholders involved, drawing on the insights of social workers and managers as well as the experiences of newcomers themselves, this book offers a unique understanding of the interactions between immigrants, the welfare state, and street-level bureaucrats. It provides valuable insights for enhancing service provision, striving for a more inclusive approach. Ebook available in Open Access. This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).